The Association between Fast Food Consumption and Obesity among College Students in Indonesia - Putri, Ulfah Mahardika Pramono; Zhang, Yuhan; Zhang, Ying; Cao, Saiying; Yang, Lina (MultiTech Publisher, 2024)
Background: In Indonesia, the total percentage of obese adults rose from 10.5% in 2007 to 21.8% in 2018. College students are the highest consumers on most food purchasing applications with fast food options. This study investigated the association between fast food consumption and obesity among college students in Indonesia. Methods: A Google Form was used to conduct a cross-sectional study with 1086 participants from March to June 2023. Food consumption was measured with the Semi-Quantitative Food Frequency Questionnaire (SQFFQ). Chi-square and Kruskal-Wallis tests were utilized. Results: The results showed that 25% of the college students were overweight and obese. Most college students (30.9%) eat fast food >4 times per week. Furthermore, 33.5% eat traditional fast food, and 28.1% eat Western fast food >2 times a week. There were significant differences in the frequency of traditional and Western fast food and energy intake of fast food after adjusting the covariates (p<0.01). The total energy consumption of fast food among obese college students in Indonesia (800.01 kcal (343.73, 1324.93)) was significantly higher than underweight (411.21 kcal (316.37, 852.13)), normal weight (417.23 kcal (311.49, 980.18)), and overweight college students (600.80 kcal (336.07, 1152.46)). Conclusions: Consuming fast food is substantially linked with obesity among college students in Indonesia. To avoid and lessen obesity among college students, eating a greater variety of healthful foods and learning to cook are necessary.